Plasmodium knowlesi-induced antigens in membranes of parasitized rhesus monkey erythrocytes. - Schmidt-Ullrich, R (1978)
Highly purified Plasmodium knowlesi schizonts were used to produce a hyperimmune anti-parasite serum in a rhesus monkey. Proteins of membranes from normal and P. knowlesi-infected erythrocytes, as well as purified schizonts, were solubilized in 1% Triton X-100 and analyzed by bidimensional electrophoretic techniques. Of seven parasite-specific antigens identified in membranes of parasitized erythrocytes by crossed immune electrophoresis against monkey anti-parasite serum, only three could be detected in the purified schizonts. Bidimensional focusing-dodecyl sulfate/polyacrylamide gel electrophoresis of membranes from parasitized cells revealed three proteins, in the 55,000-90,000 molecular weight region, with isoelectric points between pH 4.5 and pH 5.2, that could not be detected in normal membranes or purified schizonts. Membranes of normal erythrocytes and uninfected erythrocytes that had been incubated with sera from monkeys with 25-50% parasitemia did not react with the monkey anti-parasite serum.